Enhancing Student Achievement in Islamic Education: The Synergy of Teacher Recruitment, Selection, and Professional Development - Winarti, Endah; Hamzah, Akhmad Fauzi; Atqiya, Dhea Melda (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2024)
This study examines the recruitment, selection, and professional development processes of teachers aimed at enhancing student achievement. A qualitative case study approach was conducted at SMPIT YABIS, an Islamic educational institution. Data were collected through observations and interviews with five informants. The findings reveal that teacher recruitment prioritizes internal recommendations, which enhances efficiency and alignment with institutional needs. The selection process involves administrative screening, written tests, and practical teaching evaluations, emphasizing both academic competence and religious knowledge. Professional development includes structured training, support for further education, participation in professional forums (MGMP), and reward programs. Financial incentives are provided to long-serving teachers and those who successfully mentor high-achieving students, fostering motivation and commitment. These findings contribute theoretically to the discourse on human resource management in Islamic education, particularly in integrating academic and religious competencies into staffing strategies. Practically, the dual approach offers a replicable model for similar institutions, blending academic excellence with character building within faith-based education frameworks. This study underscores the critical role of motivated and well-supported teachers in achieving institutional goals and advancing student success, providing actionable insights for administrators and policymakers.